FAKTOR-FAKTOR PENYEBAB KETIDAKLENGKAPAN PENGINPUTAN KODIFIKASI PADA KASUS RAWAT JALAN DI RSUD RAJA AHMAD TABIB MENGGUNAKAN METODE DIAGRAM FISHBONE - Mulyana; Situmorang, Masriani; Rahmawati (Transpublika Publisher, 2023)
Community service at Raja Ahmad Tabib Regional General Hospital from August 14 to August 26, 2023 aims to improve the efficiency and accuracy of inputting outpatient data. This activity focused on socialization to health workers to better understand the constraints in the Raja Ahmad Tabib Regional General Hospital Management System Application. The results of observations and interviews showed several factors causing the problem. First, the number of coder personnel has not met the standard, causing data entry to be not optimal. Second, SOPs related to inputting outpatient data need to be more specific so that the process is more uniform. The literature study also shows the need for integration of information management systems to facilitate staff, but there is a gap between INA-CBGs and SIMRS at Raja Ahmad Tabib Hospital. Another problem is related to the incomplete medical record files of BPJS patients, where accident information is less specific. Emergency department assessments and history taking also did not always reflect the details of the accident. Financial constraints are the main obstacle, limiting the addition of personnel and updating the information management system which still uses a desktop. With limited budgets, resolving issues related to staffing, methods, and system integration is difficult. Special attention is needed to ensure that outpatient information management becomes more efficient and accurate.